Firm-provided training during the great recession - Bellmann, Lutz [Verfasser]; Gerner, Hans-Dieter [Verfasser]; Leber, Ute [Verfasser] (My University, 2014)
"Even though the 2008/09 economic crisis had only minor employment effects on the German labor market, it might have affected firms' further training and apprenticeship training behavior. From a theoretical point of view, the impact of the business cycle on firms' training behaviour is ambiguous. There are reasons for an increase of training during a downturn (e.g., declining opportunity costs of training, fewer exit options for trained workers) as well as arguments for a decrease of training (e.g., uncertain future benefits of training). The existing empirical evidence on the relationship between training and economic downturns is relatively scarce. In particular, we are not aware of any empirical study investigating the effects of the most recent crisis on firms' training activities in Germany. Our paper aims to fill this gap by using data from the IAB Establishment Panel, a representative German panel data set with annual information about almost 16,000 establishments. In particular, we analyzed the provision and the intensity of further training and apprenticeship training in firms which were affected by the crisis and in those which were not. Our empirical investigation revealed that the establishments, irrespective of whether or not they were hit by the economic crisis, decreased their further training and apprenticeship training efforts in 2009 compared to 2008. However, establishments directly affected by the great recession tended to reduce their training activities more often than those which were not affected. Furthermore, we found much stronger variations in the development of firms' further training activities than in the development of their apprenticeship training." (Authors' abstract, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; Betriebliche Weiterbildung; Weiterbildungsbeteiligung; Betriebliche Berufsausbildung; Ausbildungsbereitschaft; Rezession; Wirtschaftskrise; Auswirkung; IAB-Betriebspanel; Quantitative Angaben